Creating Africa in America : translocal identity in an emerging world city - Copeland-Carson, Jacqueline (Contemporary ethnography., 2004)
"'Who is 'African' in a global ecumene? Anthropologist Copeland Carson poses this challenging question in her study of cultural dynamics in Minneapolis-Saint Paul ... Highly recommended."--Choice.